2020
DOI: 10.4103/ajns.ajns_228_19
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous cerebral spinal fluid rhinorrhea with meningocele secondary to congenital foramen rotundum defect: A case report and review of literature

Abstract: Spontaneous cerebrospinal fluid (CSF) rhinorrhea is a rare occurrence. We present a case of spontaneous CSF rhinorrhea in a 57-year-old patient secondary to a sphenoid osseous defect involving the foramen rotundum and maxillary nerve with an associated arachnoid cyst and meningocele compressing the maxillary nerve. The location of the defect made correction amenable to an open skull-based approach. To the best of our knowledge, this is the first reported case of a spontaneous meningocele herniating into the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…It was reported that pneumatization of LRSS was related to the pathogenesis of SCSFR [21]. The LRSS occurred in up to 91% of the SCSFR patients whose fistula was located at the sphenoid sinus [22]. However, it is also present in 43% of normal people [7], suggesting that it is insufficient to study the overall incidence of LRSS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that pneumatization of LRSS was related to the pathogenesis of SCSFR [21]. The LRSS occurred in up to 91% of the SCSFR patients whose fistula was located at the sphenoid sinus [22]. However, it is also present in 43% of normal people [7], suggesting that it is insufficient to study the overall incidence of LRSS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, when the LRSS pneumatization is of type 3, the foramen rotundum also becomes a possible site for SCSFR. Scott et al [22] reported a case of SCSFR secondary to a congenital foramen rotundum defect. Harley et al [24] reported two cases of SCSFR whose leak sites were in the foramen rotundum.…”
Section: Discussionmentioning
confidence: 99%
“…The herniated tissue can extend to the ethmoidal sinuses or the pterygopalatine fossa. Meningoencephalocele through the foramen rotundum had been reported but without trigeminal nerve symptoms [9][10].…”
Section: Discussionmentioning
confidence: 99%